Draft Eighth Plan and Annual Plan 1991-92 Jammu and Kashmir - Planning Commission (Planning Commission, 1991)
The approved outlay for Seventh Five Year Plan (1985- 90) was Rs. 1400.00 crores. An outlay of Rs. 520.00 crores with an additionality of Rs. 30.00 crores aggregating to Rs. 550.00 crores was approved for 1989-90,the last year of the plan. The total expenditure during the Seventh Plan is of the order of Rs. 2006.23 crores.
Jammu and Kashmir